KONSEPSI KEAGAMAAN DAN KEPEMIMPINAN SUNNI VS SYIAH - IRWAN SUPRIADIN J (STIT Sunan Giri Bima, 2020)
This article is a literature study that aims to trace the literature to be able to understand the concepts of religion and leadership of Sunni vs. Shiite which has often been the subject of discussion among world academics. The problems that arise among Sunnis and Shiites are not only present on the political side, but also on the concepts of religion and leadership which also become polemic. Like the Arab Spring incident which resulted in the collapse of the power of Muammar Qadafy in Libya and Ben Ali in Tunisia, Sunni and Shia relations were also colored by differences. The conclusion of this article then shows that both Sunni and Shi'a agree that the existence of a Khilafah / Imamat government is an obligation in the lives of Muslims. Regarding the form of khilafah or government, Sunni scholars tend to be represented by Imam al-Mawardi, al-Ghazali and Ibn Kholdun tend to be accommodating towards the models of government that are carried out in the principles of deliberation both kingdom and democracy. In the Shi'ite leadership doctrine, leadership is absolute and the legal requirements of one's faith and leadership is limited to imams who are descendants of Imam Ali ibn Abi Talib, but while waiting for the presence of the